Relationship between hair shedding and systemic inflammation in COVID-19 pneumonia. (31st December 2022) - Guarnieri, Gabriella; Bertagna De Marchi, Leonardo; Marcon, Alessandro; Panunzi, Silvia; Batani, Veronica; Caminati, Marco; Furci, Fabiana; Senna, Gianenrico; Alaibac, Mauro; Vianello, Andrea
Abstract: Background: A higher risk for COVID-19 infection and severity for men compared to women has been described since the beginning of the pandemic. The role of androgens has been recently highlighted as they control two key steps of coronavirus infection mediated through the transmembrane protease serin 2 (TMPRRS2) and the angiotensin-converting enzyme 2 (ACE2) receptor in the lung tissue. Furthermore, a high incidence of androgenic alopecia among males with COVID-19 disease have been reported. Objective: This study aims to evaluate the telogen effluvium (TE) prevalence and its relationship with clinical and immunologic parameters in a sample of patients consecutively evaluated after recovery from COVID-19 pneumonia in Northern Italy. Methods: Overall 104 patients were recruited within three months from COVID-19 pneumonia recovery; 80 (77%) had been hospitalized in a Respiratory Intensive Care Unit and the remaining ones had been treated at home. The extent of TE was assessed with a visual analogic scale for thick bundle of hairs. Demographic and clinical data and systemic inflammation biomarkers were also evaluated. Results. Thirty-two patients reported a history of TE and their mean TE-VAS score was 5.78 ± 1.72 (range 3–9). Women had about a 5-fold higher risk (odds) of complaining of TE compared to males (OR = 4.69, 95%CI: 1.91, 11.49; p = .001), and the association became stronger when adjusted for COVID-19 severity (hospital admission vs home care: OR = 6.09, 95%CI: 2.34, 15.88; p < .001). Levels of C-reactive protein >1.90 mg/l (ORadj : 2.43, 95%CI 0.85, 7.05, p = 0.096) or IL 1β > 5 ng/l (ORadj 4.72, 95%CI: 1.31, 23.19, p = .03) were also significantly associated with TE. Conclusion: This exploratory study raises the hypothesis that hair shedding is more strictly related to the severity of COVID-19 disease and the underlying inflammation rather than to patients' hormonal status. KEY MESSAGES: The presence of Telogen effluvium (TE) was significantly more common in women. Higher severity of the Covid-19 disease seems to play a critical role, more important than the hormonal influence, in the development of TE. The severity of inflammation related to TE and Covid-19 could also play a role as suggested by the higher levels of CRP and platelets and IL1β.